Changes and challenges : a review of Bangladesh's development 2000 - Sobhan, Rehman; Centre for Policy Dialogue (Bangladesh) (Dhaka : Centre for Policy Dialogue : University Press, 2001)
With reference to Bangladesh.
Bangladesh economy in FY 2000 : macro economic outlook / Debapriya Bhattacharya -- Performance of the external sector in FY2000 : growth dynamics and emergent concerns / Mustafizur Rahman -- Recent development and structural changes in Bangladesh agriculture : issues for reviewing strategies and policies / Mahabub Hossain -- The state of governance in Bangladesh / Rehman Sobhan -- Rethinking anti-poverty / Binayak Sen -- Development of gas sector in Bangladesh : status, policy options and challenges / Azim Uddin Ahmed -- Power sector restructuring in Bangladesh / Nuruddin Mahmud Kamal.
Includes statistical tables.
Includes bibliographical references (pages 138-139).
BIED
Complimentary copy from BIED, Donated By Akbar Ali Khan
Keywords: Bangladesh -- Economic conditions; Bangladesh -- Economic policy -- Econometric models; Economics